Do Firm Size, Corporate Governance, and Tax Panning Effect on Earning Management? - Djama, Hardiyanti; Madjid, Suhirman (Santoso Academy Network, 2024)
This research aims to test the influence of firm size, good corporate governance, and tax planning on earnings management. The type of research used is quantitative descriptive verification research. This research uses a sample of retail firms in the Food Retail and Distributors, Supermarkets and Convenience Stores, and Electronics Retail sectors, which are listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique in this research is purposive sampling with a sample size of 40 firms. This research uses secondary data, namely firm financial reports obtained from the official websites www.idx.co.id and www.idnfinancials.com. The analytical method used is multiple linear. The results of this research indicate that firm size, corporate governance, and tax planning do not affect earnings management. The managerial implication of this research is that firm managers need to understand that firm size, CG, and tax planning are interrelated in influencing earnings management. Managers must ensure that the tax management strategies used do not violate GCG principles and remain within the corridors of applicable tax regulations earning.